Synthesis of aspirin-chalcone derivatives and their antibacterial activity - Lim, Ji Yuan (Universiti Malaysia Sarawak, (UNIMAS), 2015)
Aspirin and chalcone have long been used for its medicinal purpose due to its biological activity. This research focused on the synthesis of aspirin-chalcone derivatives resulting from the reactions of chalcone intermediate with acetylsalicyloyl chloride. Aspirinchalcone derivatives have been synthesized. The successfully synthesized compounds were characterized using FTIR, 1H NMR and 13C NMR. Antibacterial assay was carried out using disc diffusion method against the growth of Escherichia coli ATCC 29522. However, the result indicated that the newly synthesized aspirin-chalcone derivatives showed no antibacterial activity against E.coli.